Analisis Perbandingan Kinerja Keuangan Bank Syariah dengan Bank Konvensional Perspektif Maqashid Syariah - Hidayat, Solikhul; Saiban, Kasuwi; Nurfadilah, Nurfadilah; Munir, Misbahul (Institut Agama Islam Negeri Ponorogo, 2022)
Accounting as a complement (tahsiniyat) can turn into a necessity (hajiyat) at the maqashid level. Maqashid sharia is not the most decisive factor in giving birth to sharia economic products that can play a dual role as a tool of social control and socio-economic engineering to realize human benefit, sharia maqashid can provide philosophical and rational dimensions to sharia economic law products that are born in economic ijtihad activities contemporary sharia. Islamic banking, which is growing and developing in the country, is currently increasingly in demand by investors and potential investors. However, the problem is that people do not know how far the performance of Islamic banking is, when compared to the performance of conventional banks which first operated. This study is intended to compare the performance of the two banks, this is important so that investors, potential investors know and assess the performance of the two banks. Assessment of financial performance can be seen from the financial ratios of CAR, ROA, ROE, NPL, LDR, and BOPO. The research population is 14 Islamic commercial banks. The sample using purposive sampling, using 3 Islamic banks, Bank Negara Indonesia (BNI) Syariah, Bank Rakyat Indonesia (BRI) Syariah, Bank Mandiri Syariah and 115 conventional banks. Research data from the annual financial statements of the banks under study. The data analysis technique used the Mann-Whitney U Test. The results showed that there was no significant difference in the CAR ratio between Islamic banks and conventional banks. The ratio of ROA, ROE, NPL, LDR and BOPO there are significant differences between Islamic banks and conventional banks. The financial performance of Islamic banks is better in terms of the LDR ratio, while the financial performance of conventional banks is better in terms of the ratios of CAR, ROA, ROE, NPL, BOPO.